188k views
5 votes
Y=4x y=-2x-6 how to sovle this

User DaGo
by
5.3k points

1 Answer

4 votes

Answer:


Explanation:


Substitute 4x for Y: 4x = -2x -6


Now add 2x to both sides

(due to reciprocal, the opposite of -2x is positive 2x): 4x + 2x = -2x +2x -6


Add common like terms

(4x + 2x = 6x and -2x + 2x cancel out leaving -6 alone): 6x = 6


Now get X alone by dividing the 6 to both sides: 6x/6 = -6/6


Since you're dividing a negative and a positive, the outcome will be a negative so the answer is: X= -6


Hope this helps :)

User Love Kumar
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.